Power in Numbers: Fair Trade as a Civil Society Alternative to Neoliberal Free Trade - Clewes, Lauren (Glendon Journal of International Studies, 2020)
Abstract: This paper examines fair trade as a more positive alternative to the free trade framework that currently pervades the global economy, and as a critique of the wider neoliberal economic paradigm, through secondary research and analysis. The existing free trade model is outdated, perpetuates capitalist hegemony and maintains an oppressive consumerist mindset that is incompatible with an ethical and sustainable future. Fair trade is one potential civil society alternative that already has positive and tangible impacts that should be expanded and refined. This article explores neoliberalism and its drawbacks while presenting fair trade as a critique and possible replacement. It is hoped that this paper stimulates discussion on the negative impacts of the hegemonic neoliberal economic system and the merits of fair trade and incites thought into other possible alternatives for a more inclusive, ethical and sustainable future. Résumé : Cet article examine le commerce équitable comme un choix plus positif au cadre de libre-échange qui envahit actuellement l’économie mondiale et présent une critique du paradigme néolibéral au sens large, à travers les recherches et l’analyse secondaire. Le modèle de libre-échange est démodé, perpétue l’hégémonie capitaliste et maintient un état d’esprit de consommateur oppressif incompatible avec un avenir éthique et durable. Le commerce équitable est une alternative potentielle de la société civile qui a déjà des impacts positifs et tangibles qu’il convient d’étendre et d’affiner. Cet article également explore le néolibéralisme et ses inconvénients et présente le commerce équitable comme une critique et une alternative possible. Nous espérons que ce document ouvrira une discussion sur des impacts négatifs du système économique néolibéral hégémonique et des avantages du commerce équitable et incitera d’autres solutions pour un avenir plus inclusif, éthique et durable.